Achievement of complete morphological regression in the use of trastuzumab in patients with inoperable locally advanced Her-2+ breast cancer - K. R. Zeinalova; Ya. V. Vishnevskaya; I. P. Ganshina (ABV-press, 2014)
Objective: to evaluate the efficiency (morphological tumor complete regression (mCR), a clinical effect) and safety of the use of new anthracycline-free neoajuvant chemotherapy regimens (paclitaxel + vinorelbine and docetaxel + carboplatin) in combination with trastuzumab in patients with Stage IIIa-c breast cancer (BC) and Her-2 hyperexpression.Subjects and methods. The study enrolled 36 Stage IIIa-c BC patients receiving 4-8 cycles of a chemotherapy regimen of paclitaxel (100 mg/m2) + vinorelbine (25 mg/m2) (every 3 weeks) or docetaxel (50 mg/m2) + carboplatin (AUC 5) (every 3 weeks) in combination with trastuzumab.Results. The docetaxel (75 mg/m2) + carboplatin (AUC 5) + trastuzumab regimen demonstrated a high effectiveness with acceptable toxicity. Seventeen (58.8 %) patients achieved mCP. The clinical effect was 83.3 % (4 complete and 11 partial tumor regressions).The paclitaxel (135 mg/m2) + vinorelbine (25 mg/m2) (every 3 weeks) + trastuzumab regimen is efficacious and promising when the doses of the drugs are increased and granulocyte colony-stimulating factor used.